The classic Jewish philosophers : from Saadia through the Renaissance - Schweid, Eliezer, 1929-2022 (Supplements to The journal of Jewish thought and philosophy, 2008)
Provides a reference of the major medieval Jewish philosophers, as well as an eminently readable narrative of the course of medieval Jewish philosophical thought, presented as a response to the spiritual-intellectual challenges.